Screening of probiotic bacteria and its role on artificial infection of Vibrio harvey in white shrimp (Litopenaeus vannamei) - Sukenda, .; Sihombing, A.J.; Novianti, Fitria; Widanarni, . (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
Probiotic was screened from 28 strains of normal bacterial flora isolated from rearing water in a Litopenaeus vannamei farm based on its inhibitory activity against the growth of Vibrio harveyi. Antibacterial activity was also tested in vivo to V. harveyi in L. vannamei. The result showed that the probiotic has a antibacterial effect on V. harveyi. The in vivo test showed that shrimps injected with probiotic previously before challenged with V. harveyi has survival higher than control. Probiotic isolate was suspected as Vibrio furnissi. Keywords: biocontrol, inhibitory activity, Vibrio furnissi, Vibrio harveyi, Litopenaeus vannamei AbstraK Bakteri probiotik ditapis dari 28 strain bacteria flora yang diisolasi dari air pemeliharaan udang vaname Litopenaeus vannamei berdasarkan aktivitas penghambatannya terhadap pertumbuhan Vibrio harveyi. Aktivitas bakteri probiotik juga diuji secara in vivo terhadap V. harveyi pada udang putih. Hasil penelitian menunjukkan bahwa bakteri probiotik isolat memiliki kemampuan antibakteria terhadap V. harveyi. Uji in vivo menunjukkan bahwa udang yang diinjeksi probiotik sebelum diuji tantang dengan V. harveyi memiliki kelangsungan hidup lebih tinggi daripada kontrol. Isolat probiotik tersebut diduga adalah Vibrio furnissi. Kata kunci: biokontrol, aktivitas penghambatan, Vibrio furnissi, Vibrio harveyi, Litopenaeus vannamei